1998
DOI: 10.1111/j.1440-1819.1998.tb03272.x
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of the mental health of young migrant workers in Shenzhen

Abstract: The aim ofthis study is to examine the mental health status ofyoung migrant workers in Shenzhen.Using the Syniptonis Check List-90 (SCL-90), Eysenck Personality Questionnaire, Social Support Scale and Mental Health Questionnaire for Laborers,371 migrant workers who came from inland areas ofChina and 100 local workers Xvere investigated.The SCL-90 profile of migrant workers was also compared to the SCL-90 n o r m provided by general people in China. The SCL-90 results showed that the total scores, the average s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 2 publications
3
29
1
Order By: Relevance
“…This gap suggests that migrant workers have relatively poor mental health. Moreover, it corroborates previously reported findings that rural-urban migrant workers not only have elevated stress levels, but experience more psychological problems (Shen et al 1998;Li et al 2006;Hu and Gu 2008;Jiang et al 2007). These problems may partially stem from a persistently depressed socioeconomic status, which ensues from denial of certain rights of citizenship at the urban destination.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This gap suggests that migrant workers have relatively poor mental health. Moreover, it corroborates previously reported findings that rural-urban migrant workers not only have elevated stress levels, but experience more psychological problems (Shen et al 1998;Li et al 2006;Hu and Gu 2008;Jiang et al 2007). These problems may partially stem from a persistently depressed socioeconomic status, which ensues from denial of certain rights of citizenship at the urban destination.…”
Section: Discussionsupporting
confidence: 92%
“…There are limited data on the mental health status of Chinese rural-urban migrants. One study examined mental health symptoms among 371 (166 males and 205 females) migrant workers in Shenzhen, China (Shen et al 1998). These migrant workers manifested poorer mental health than their nonmigrant counterparts and the general Chinese population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast with the findings of other international studies and Shenzhen-based studies (Shen et al, 1998), we found no gender differences in clinically relevant DS status. Previous studies found that females were at higher risk of developing depression compared with their male counterparts because of artefactual and genuine determinants of gender differences (Piccinelli & Wilkinson, 2000).…”
Section: Discussioncontrasting
confidence: 83%
“…The other groups have unmarried women who have undergone abortion (Zhang et al (2010)), earthquake survivors (Wang et al 2000), young migrant workers (Shen et al 1998), etc. The SCL-90 results of different groups of different occupations are different.…”
Section: Mental Health Measurement and Scl-90mentioning
confidence: 98%